Chronic Subordination Stress Induces Hyperphagia and Disrupts Eating Behavior in Mice Modeling Binge-Eating-Like Disorder - Razzoli, Maria (Front Nutr, 2015)
Background: Eating disorders are associated with physical morbidity and appear to have causal factors like stressful life events and negative affect. Binge-eating disorder (BED) is characterized by eating in a discrete period of time a larger than normal amount of food, a sense of lack of control over eating, and marked distress. There are still unmet needs for the identification of mechanisms regulating excessive eating, which is in part due to the lack of appropriate animal models. We developed a naturalistic murine model of subordination stress-induced hyperphagia associated with the development of obesity. Here, we tested the hypotheses that the eating responses of subordinate mice recapitulate the BED and that limiting hyperphagia could prevent stress-associated metabolic changes. Methods: Adult male mice were exposed to a model of chronic subordination stress (CSS) associated with the automated acquisition of food intake and we performed a detailed meal pattern analysis. Additionally, using a pair-feeding protocol we tested the hypothesis that the manifestation of obesity and the metabolic syndrome could be prevented by limiting hyperphagia. Results: The architecture of feeding of subordinate mice was disrupted during the stress protocol due to disproportionate amount of food ingested at higher rate and with shorter satiety ratio than control mice. Subordinate mice hyperphagia was further exacerbated in response to either hunger or to the acute application of a social defeat. Notably, the obese phenotype but not the fasting hyperglycemia of subordinate mice was abrogated by preventing hyperphagia in a pair-feeding paradigm. Conclusion: Overall, these results support the validity of our CSS to model BED allowing for the determination of the underlying molecular mechanisms and the generation of testable predictions for innovative therapies, based on the understanding of the regulation and the control of food intake.